2017
DOI: 10.1002/rnc.3721
|View full text |Cite
|
Sign up to set email alerts
|

Finite time control of robotic manipulators with position output feedback

Abstract: Summary This paper deals with the robust finite time tracking of desired trajectories for a wide group of robotic manipulators in spite of unknown disturbances, uncertainties, and saturations of actuators while only manipulator's positions are available and its velocities are not measurable physically. A new form of chattering‐free second order fast nonsingular terminal sliding mode control scheme is introduced to design input torques for fulfilling the determined tracking objective in the adjustable total fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…To effectively settle this issue, a novel STA with TDE was proposed for robot manipulators recently . Exciting results were reported with this method, but improvement can still be made for better performance in the following two aspects: (1) the robust term used in the work of Kali et al, was traditional SM control with linear error dynamics, which may result in slow convergence and low control accuracy around the equilibrium point, and it has been demonstrated that terminal SM (TSM) control can ensure better control performance than the traditional SM one; and (2) the standard STA was used and may lead to relative poor performance under the situation that system states are far from the equilibrium point.…”
Section: Introductionmentioning
confidence: 99%
“…To effectively settle this issue, a novel STA with TDE was proposed for robot manipulators recently . Exciting results were reported with this method, but improvement can still be made for better performance in the following two aspects: (1) the robust term used in the work of Kali et al, was traditional SM control with linear error dynamics, which may result in slow convergence and low control accuracy around the equilibrium point, and it has been demonstrated that terminal SM (TSM) control can ensure better control performance than the traditional SM one; and (2) the standard STA was used and may lead to relative poor performance under the situation that system states are far from the equilibrium point.…”
Section: Introductionmentioning
confidence: 99%
“…Since this work is an extension of the work in [25], the finite time robust controller (FTRC) presented in [25] is selected for the comparisons. The control gains of the FTRC in [25], NFTSMC (11), and ANFTSMC (21) are given in TABLE 1. The simulation results under the three controllers are shown in Figures 2-4.…”
Section: Simulationmentioning
confidence: 99%
“…Finite-time convergence can stabilize system states to equilibrium points in a finite time, which is superior to asymptotic stability or aconvergence [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20] Originally, linear error dynamics were combined with TDE leading to asymptotic stability, which, however, is not robust enough for some complex systems under strong lumped disturbance. Thus, the terminal sliding mode (TSM) control and its improved version, [21][22][23][24][25][26][27] which can ensure finite-time stability and high tracking precision, were integrated with TDE. [28][29][30] These TDE-based TSM controllers can effectively take advantage of TDE and TSM techniques, resulting in model-free robust controllers while still conquering the practical limitations of their own.…”
Section: Introductionmentioning
confidence: 99%